2008
DOI: 10.24200/jeps.vol2iss1pp98-144
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of the good language teacher as perceived by prospective teachers of English in the Arab World

Abstract: The purpose of this study was to identify the qualities of the good language teacher as perceived by student teachers of English in the Arab World. In Fall 2006, a questionnaire including 69 qualities of the good language teacher representing three dimensions (knowledge, teaching skills and personality) was developed, validated and administered to 273 prospective teachers of English in three countries of the Arab world (Egypt, Oman and Saudi Arabia). ANOVA test results indicated that there were statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
5
2
Order By: Relevance
“…This is considered beneficial as the participants conceived that appropriate and effective utilization of technology will obviously ease teachers to qualify the students with skills to confront their future lives. However, this finding is contrastive to Abu-Rahma's (2008) which mentioned that utilizing the latest technology in teaching is moderately important. With respect to this finding, he further visualized that it might be due to the participants' belief that language teachers can effectively teach without having any sophisticated educational technology.…”
Section: 7%contrasting
confidence: 73%
“…This is considered beneficial as the participants conceived that appropriate and effective utilization of technology will obviously ease teachers to qualify the students with skills to confront their future lives. However, this finding is contrastive to Abu-Rahma's (2008) which mentioned that utilizing the latest technology in teaching is moderately important. With respect to this finding, he further visualized that it might be due to the participants' belief that language teachers can effectively teach without having any sophisticated educational technology.…”
Section: 7%contrasting
confidence: 73%
“…Research on effective EFL teachers has revealed a number of qualities that contribute to students’ language learning success. These qualities have mostly revolved around a number of categories: personality, language knowledge, teaching methods, organization and communication skills, and socioaffective skills (Abu-Rahmah, 2008; Al-Mahrooqi et al, 2015; Baytur & Razi, 2015; Brosh, 1996; Febriyanti, 2018; Gabrielatos, 2002; Park & Lee, 2006; Salahshour & Hajizadeh, 2013; Taqi et al, 2015; Wichadee, 2010). In addition, having reviewed literature on the effectiveness of EFL teachers, Al-Seghayer (2017) summarized those qualities into five main categories: cognitive knowledge, content knowledge, language proficiency, personality traits, and other related key variables that can be achieved through a number of channels, including initiatives and training programs and support and professional development opportunities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The gender has been correlated with students’ and teachers’ choices of EFL teacher effectiveness and various findings have been revealed. Some studies reported differences in the choices of respondents attributed to genders (Abu-Rahmah, 2008; Chen & Lin, 2009; Ramazani, 2014; Taqi et al, 2015). However, some other studies showed that the genders did not have any effect on the respondents’ choices regarding the qualities of effective EFL teacher (Nghia, 2015; Wichadee, 2010).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations